Charge-equalisation for Li-ion batteries by direct charge-transfer circuit. Issue 12 (2nd December 2017) - Hsieh, Yao-Ching; Wu, Wei-Ting; Chiu, Yu-Chun
ABSTRACT: This paper proposes a charge-equalisation circuit for series-connected battery pack based on direct charge transference. The battery cells inside the pack can mutually transfer their charges directly via the bidirectional flyback converter within this proposed charge-equalisation circuit. Since electric charge is transferred directly between the highest and lowest charged cells, the losses dissipated during the transfer processes can be minimised. Meanwhile, the equalisation time can be reduced. A battery-management IC is used to detect the cell voltages and drive the battery-selection switches. A battery pack that consists of four series-connected Li-ion battery cells is used in the experiment. The charge-equalisation circuit topology and its control scheme are verified by experiments. From the experimental results, the proposed circuit is able to shrink the maximum voltage difference between cells into 30 mV range after 170min. The results successfully verify the feasibility of the circuit topology and the control scheme.